Investigation of the coexistence of CKD and non-communicable chronic diseases in a PBM company in South Africa - W. P. Meuwesen (AOSIS, 2016)
Background: Chronic kidney disease (CKD) is a public health problem, with increasing global prevalence. Several factors could influence the prognosis of CKD, including comorbid chronic conditions. This study investigated the coexistence of CKD and noncommunicable chronic diseases in the private health sector of South Africa.